Channel Modeling and MIMO Capacity for Outdoor Millimeter Wave Links - Hong Zhang; Venkateswaran, Sriram; Madhow, Upamanyu (2010 IEEE Wireless Communication and Networking Conference, 2010)
Recent work has shown that mesh networks based on short-range outdoor millimeter (mm) wave links in the unlicensed 60 GHz band are a promising approach to providing an easily deployable broadband infrastructure. In this paper, we investigate the robustness of such links, focusing in particular on the effect of multipath fading resulting from reflections from the ground and building walls for a lamppost deployment of mm wave nodes. Our ray tracing based model shows that, while only a small number of paths are significant for the highly directional links considered, they can cause significant fluctuations in the received signal strength. Our simulations show that 10-20 dB fades below the benchmark of free space propagation can occur quite easily (e.g., 5-15% of the time, averaging across typical deployment scenarios), and that the received power is extremely sensitive to small variations in geometry (e.g., altering the position of the antenna by 1 cm can reduce the received power as much as 46.7 dB). We also demonstrate, however, that extremely robust performance can be obtained by employing multiple antennas at appropriately chosen separations, using standard space-time communications strategies such as transmit precoding (when the transmitter knows the channel) and space-time coding (when the transmitter does not know the channel).